The prognostic impact of Her2 status in early triple negative breast cancer: a Turkish Oncology Group (TOG) study - Ozyurt, Neslihan; Alkan, Ali; Gulbagci, Burcu; Seyyar, Mustafa; Aydin, Esra; Sahbazlar, Mustafa; Dogan, Mutlu (Nature Portfolio, 2024)
The studies evaluating the impact of Her2 levels in neoadjuvant setting have conflicting data. The aim of the study was to evaluate the prognostic impact of Her2 status in early triple negative breast cancer(TNBC). In the study TNBC patients who were treated with neoadjuvant chemotherapy (NAC) and surgery were analyzed retrospectively. The primary aim of the study was to analyze the impact of Her2 status(Her2-0 and Her2-low) on pathological complete response (pCR). The secondary objectives were disease free survival (DFS) and overall survival (OS). 620 female triple negative breast cancer patients were evaluated. 427 patients (68.9%) had Her2-0 and 193(31.1%) had her2-low pathology. The pCR rates were similar between Her2-0 and Her2-low patients (33.0% vs. 27.5%, p = 0.098). Although Her2-0 group has better DFS (106 vs. 50 months, p = 0.002), in multivariate analysis it had a HR of 0.74 (p = 0.06). In addition, OS was similar (131 vs. 105 months, p = 0.13) with a HR of 0.88 (p = 0.61). In multivariate analysis; presence of LVI (HR:2.2 (95% CI 1.1-3.5) p = 0.001), Clinical stage T1/T2 (HR:0.39 (95% CI 0.2-0.6) p < 0.001) and lymph node negativity (HR:0.35 (95% CI 0.1-0.9) p = 0.03) were independent factors for OS. Although there were pathological and clinical differences, the pCR, DFS and OS were similar between Her2-0 and Her2-low TNBC patients. The importance of Her2 status of TNBC in neoadjuvant setting should be further studied.
Keywords: Pathological Complete Response; Neoadjuvant Chemotherapy; Hormone-Receptor; Expression; Survival